Improved management of acute kidney injury in primary care using e-alerts and an educational outreach programme. (28th April 2018) - Tollitt, James; Flanagan, Emma; McCorkindale, Sheila; Glynn-Atkins, Sam; Emmett, Lauren; Darby, Denise; Ritchie, James; Bennett, Brandon; Sinha, Smeeta; Poulikakos, Dimitrios
Abstract: Purpose: Acute kidney injury (AKI) detected in primary care is associated with increased morbidity and mortality. AKI electronic alerts (e-alerts) and educational programmes have recently been implemented but their contribution to improve AKI care is unknown. This project aimed to improve response to AKI detected in primary care and used a factorial design to evaluate the impact of the UK National Health Service (NHS) AKI e-alert and AKI educational outreach sessions on time to response to primary care AKI stages 2 and 3 between April and August 2016. Methods: A total of 46 primary care practices were randomized into four groups. A 2 × 2 factorial design exposed each group to different combinations of two interventions. The primary outcome was 'time to repeat test' or hospitalization following AKI e-alert for stages 2 and 3. Yates algorithm was used to evaluate the impact of each intervention. Time to response and mortality pre- and post-intervention were analysed using Mann–Whitney U test and chi-square test respectively. The factorial design included two interventions: an AKI educational outreach programme and the NHS AKI e-alerts. Results: 1807 (0.8%) primary care blood tests demonstrated AKI 1–3 (78.3% stage 1, 14.8% stage 2, 6.9% stage 3). There were 391 stage 2 and 3 events from 251 patients. E-alerts demonstrated a reduction in mean response time (–29 hours). Educational outreach had a smaller effect (–3 hours). Median response time to AKI 2 and 3 pre- and post-interventions was 27 hours versus 16 hours respectively ( P = 0.037). Stage 2 and 3 event-related 30-day all-cause mortality decreased following the interventions (15.6% versus 3.9% P = 0.036). Conclusion: AKI e-alerts in primary care hasten response to AKI 2 and 3 and reduce all-cause mortality. Educational outreach sessions further improve response time.